2011
DOI: 10.1002/adsc.201100446
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Protein Engineering of Biocatalysts for Organic Synthesis

Abstract: Modern tools for enzyme discovery and protein engineering substantially broadened the number of enzymes applicable for biocatalysis and helped to alter their properties such as substrate range, enantioselectivity, and stability under process conditions. In addition, these methods also enabled one to explore reactions for organic synthesis for which no suitable enzymes were available until recently. This review provides a summary of the different concepts and technologies, which are exemplified for various enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 264 publications
(290 reference statements)
0
46
0
5
Order By: Relevance
“…To overcome these limitations, structure-based protein engineering has been often successfully applied to meet desired biochemical needs (Behrens et al 2011). Yun et al (2005) reported a (S)-selective mutant of V. fluvialis 5-TA which showed reduced product inhibition by aliphatic ketone.…”
Section: Protein Engineeringmentioning
confidence: 99%
“…To overcome these limitations, structure-based protein engineering has been often successfully applied to meet desired biochemical needs (Behrens et al 2011). Yun et al (2005) reported a (S)-selective mutant of V. fluvialis 5-TA which showed reduced product inhibition by aliphatic ketone.…”
Section: Protein Engineeringmentioning
confidence: 99%
“…The improved variants H201S and H201S/K168I showed, respectively, 60% and 100% improved stability towards octanal, while preserving the specific activity of the wt enzyme. M A N U S C R I P T ACCEPTED MANUSCRIPT 7 …”
Section: Improving Lipase Stability By Protein Engineeringmentioning
confidence: 99%
“…Several comprehensive reviews discussed the discovery and engineering tools developed to obtain naturally evolved or tailor-made enzymes with enhanced properties for chemical synthesis [29,30,40]. In the case of microbial strains isolated from natural environment, enzymes could be discovered through protein purification, insertional mutation, chromosome walking, shotgun library, etc.…”
Section: Discovery and Characterization Of Opbe Reductasesmentioning
confidence: 99%
“…Various enzyme discovery and protein engineering tools have been proposed and proved, which would greatly shorten the developing period and increase the availability of robust enzymes. Several literatures on the biocatalytic asymmetric reduction for pharmaceuticals, protein engineering strategies for robust enzymes in chemical synthesis have been reviewed [28][29][30][31][32]. Also, various OPBE reductases have been successfully identified from natural samples or genome databases.…”
Section: Introductionmentioning
confidence: 99%